Pengaruh Media Grafis Berbasis Canva Terhadap Hasil Belajar Siswa Kelas IV Gugus XIV Kota Bengkulu - Oktavia, Fayza; Dalifa; Kurniawati, Ike (JURIDIKDAS, 2024)
The purpose of this study is to ascertain how using graphic media applications based on Canva affects the learning outcomes of IPAS students in fourth grade in Cluster XIV, Bengkulu City. This kind of study employs a quasi-experimental approach with a matching only pretest-posttest group design and is quantitative in nature. Bengkulu City's SDN Cluster XIV is the study's population. In this study, fourth-grade children from SDN 42 Bengkulu City served as the experimental group and fourth-grade students from SDN 45 Bengkulu City served as the control group. Multiple-choice test questions were employed in the study instrument. Descriptive analysis, precondition testing, and inferential analysis—specifically, the t-test—are the methods of data analysis that are employed. The study's findings show a substantial difference between the data from the pretest and posttest. The values of t count = 3.336, Sig. (2-tailed) = 0.002, and t-table distribution = 1.686 support this conclusion. The t-count value (3.336 > 1.686) and the two-tailed significance level (0.002 < 0.05) are thus greater. Ha is thus accepted whereas H0 is refused. Based on the study's findings, it can be inferred that IPAS students in fourth grade of Cluster XIV, Bengkulu City, benefit from using Canva-based graphic media applications in their learning outcomes.